Development of Electronic Student Worksheet Based on CORE (Connecting, Organizing, Reflecting and Extending) on Hydrocarbon Materials - Huriyah, Hikmah Salamah; Linda, Roza; Herdini, Herdini (Journal of Educational Sciences, 2025)
This study aims to produce a valid and usable CORE-based E-LKPD on hydrocarbons. This study was conducted at two schools, namely SMAN 6 Pekanbaru and SMAN 7 Pekanbaru. The study was motivated by students' difficulties in learning chemistry, particularly the hydrocarbon material, due to the teaching materials used being monotonous, poorly designed, and failing to utilize the rapidly advancing technology available today. This study includes validation and limited testing. This study used an R&D development research design with a modified 4-D model (Define, Design, Develop, Disseminate) into a 3-D model (Define, Design, Develop). The research results based on validation by content validators regarding content suitability, CORE characteristics, language, presentation, and graphics, respectively, achieved suitability scores with an average of 100%, indicating validity. Meanwhile, the validation results by media validators based on the aspects of appearance and software utilization had a feasibility score of 98.43% on average. The results of the responses from chemistry teachers and limited group trials obtained average percentages of 98.75% and 87.49%, respectively, with valid criteria. This shows that the CORE-based E-LKPD on the subject of hydrocarbons is practically used as teaching material in the learning process and students are more interested in learning hydrocarbon material.